Zinc Oxide (ZnO) Nanoparticles from Eichhornia Crassipes for Inactivating Pathogenic Bacteria in Greywater - Safuan, Muhammad Eizwan; Radin Mohamed, Radin Maya Saphira; Mohamad Asraf Nordin (International Journal of Integrated Engineering, 2025)
Pathogenic bacteria are dangerous bacteria found in greywater produced from household activities. E. Coli and S. aureus are among bacteria that have become an environmental issue and cause negative impact to the ecosystem. The ZnO nanoparticles (NPs) have been found as good deactivating agents for bacteria in greywater. This research examines how pathogenic bacteria in greywater can be neutralized by utilizing ZnO NPs derived from the aquatic grass, Eichhornia crassipes. E. Coli and S. aureus were made using the serial dilution technique by successive resuspension in predetermined amounts of liquid diluent. E. Coli and S. aureus were mature by culture on the agar plate. The pathogenic inactivation efficiency of ZnO NPs was optimized by varying ZnO NPs dosage and irradiation time using Response Surface Methodology (RSM). The microstructural analysis demonstrated that the ZnO involved of bigger and smaller particles with sizes in the scale of 51.9 nm to 31.0 nm. The greatest inactivation efficiency of ZnO-E. crassipes for bacteria in greywater was 3.498 log for E. Coli and 3.368 log for S. aureus. The ZnO-E. crassipes has the potential to inactivate pathogenic bacteria.